1994
DOI: 10.1093/jnci/86.10.770
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cancer Growth in Mice Administered Daily Human-Equivalent Doses of Some H1-Antihistamines: Predictive In Vitro Correlates

Abstract: These in vitro tests may prove valuable to screen potential tumor growth promoters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 0 publications
2
35
1
Order By: Relevance
“…Other tricyclic analogues of amitriptyline, clomipramine and desipramine, exhibited the same properties (81,82). Also, several antihistamines enhanced melanoma and fibrosarcoma in mouse in vitro assays (83).…”
Section: Promoters and Protective Agentsmentioning
confidence: 87%
“…Other tricyclic analogues of amitriptyline, clomipramine and desipramine, exhibited the same properties (81,82). Also, several antihistamines enhanced melanoma and fibrosarcoma in mouse in vitro assays (83).…”
Section: Promoters and Protective Agentsmentioning
confidence: 87%
“…Promethazine inhibits the effect of histamine on endotoxins against certain solid tumors (25). Another report suggests that certain H1 antagonists increase the growth rate of melanoma and fibrosarcoma cell lines (26). In any case it is now well documented by animal studies and clinical data that H1 receptor antagonists do not promote tumor formation (27).…”
Section: Discussionmentioning
confidence: 99%
“…No increased risk of breast cancer was evident with the use of these medications. Most notably, the use of astemizole (ORϭ1.08, 95% CI: 0.64, 1.82) or loratadine (ORϭ0.92, 95% CI: 0.74, 1.15), both associated with enhanced tumor growth in the Brandes study, 2 were not significantly associated with breast cancer. No indication of effect modification by menopausal status was apparent for regular use of antihistamines (data not shown).…”
Section: Resultsmentioning
confidence: 91%
“…1 The other study found that mice injected with melanoma or fibrosarcoma cells experienced accelerated tumor growth with the administration of human equivalent doses of the antihistamines loratidine and astemizole (for melanoma and fibrosarcoma), and hydroxyzine (for melanoma). 2 Animal data are suggestive of the effect that these medications might have on humans. As a result, following the publication of these results, epidemiologic studies have used human populations to explore the hypothesis that there may be a relationship between cancer risk and the use of antidepressants, and, to a lesser degree, antihistamines.…”
mentioning
confidence: 99%